Whole‐exome sequencing identified novel compound heterozygous variants in a Chinese neonate with liver failure and review of literature. Issue 12 (18th November 2020) - Qin, Zailong; Yang, Qi; Yi, Shang; Huang, Limei; Shen, Yiping; Luo, Jingsi
Abstract: Background: Liver failure caused by TRMU is a rare hereditary disorder and clinically manifests into metabolic acidosis, hyperlactatemia, and hypoglycemia. Limited spectrum of TRMU pathogenic variants has been reported. Methods: Whole‐exome sequencing was employed for the diagnosis of a 5‐day‐old female who suffered from severe neonatal hyperlactatemia and hypoglycemia since birth. Sanger sequencing was performed to confirm the origin of the variants subsequently. Variants classification was followed to ACMG guideline. Results: A compound heterozygosity of a frameshiftc.34_35dupTC (p.Gly13fs) and a missense c.244T>G (p.Phe82Val) in TRMU was detected, both variants are novel and pathogenic. Analysis of clinical and genetic information including patients reported previously indicated that there is no significant correlation between the genotype and the phenotype of TRMU‐caused liver failure. Conclusion: To the best of our knowledge, this is the first case report of TRMU‐caused liver failure in China. Whole‐exome sequencing is effective for conclusive diagnosis of this disorder and beneficial for its clinical management. Abstract : Liver failure caused by TRMU is a rare hereditary disorder. Here, we report the first case of TRMU‐related liver failure in China. We suggest that TRMU deficiency should be considered when ALF was presented with hyperlactatemia, hypoglycemia, and metabolic acidosis in infants. l ‐cysteine and N‐acetylcysteine should be considered in clinical treatment of patients diagnosed with TRMU mutation.